PELATIHAN PENINGKATAN KETERAMPILAN MENULIS KARYA SASTRA DAN ILMIAH BAGI SISWA SEKOLAH MENENGAH PERTAMA SEKOTA METRO - Nurlaksana Eko Rusminto; Sumarti; Rian Andri Prasetya; Fajar Riyantika (Jurusan Pendidikan Bahasa dan Sastra Indonesia, FKIP Universitas Lampung, 2022)
This training activity to improve the skills of writing literary and scientific works for junior high school students throughout Metro City aims to: (1) increase literary and linguistic knowledge, (2) improve the ability to write literary works and scientific works. This activity has increased literary and linguistic knowledge, as well as improved the ability to write literary works among junior high school students in Metro City. The existence of training to improve the skills of writing literary and scientific works is expected to foster motivation and increase the enthusiasm of the participants to write various sources of inspiration into literary and scientific works. This motivation can grow, among other things, due to the meeting of children's writers, where they can feel the joy of being a writer. They are also increasingly convinced that anyone who means it can become a writer. In addition, the participants also obtained an overview of the procedure for publishing works to various print media. Kegiatan pelatihan peningkatan keterampilan menulis karya sastra dan ilmiah untuk siswa SMP se-Kota Metro ini bertujuan untuk: (1) meningkatkan pengetahuan kesastraan dan kebahasaan, (2) meningkatkan kemampuan menulis karya sastra dan karya ilmiah. Kegiatan ini telah meningkatkan pengetahuan kesastraan dan kebahasaan, serta meningkatkan kemampuan menulis karya sastra di kalangan siswa SMP di Kota Metro. Adanya pelatihan peningkatan keterampilan menulis karya sastra dan ilmiah ini diharapkan menumbuhkan motivasi dan meningkatkan semangat para peserta untuk menuliskan berbagai sumber ilham menjadi karya sastra dan ilmiah. Motivasi ini dapat tumbuh di antaranya disebabkan adanya jumpa penulis anak, di mana mereka bisa merasakan senangnya menjadi seorang penulis. Mereka pun semakin yakin bahwa siapa saja yang bersungguh-sungguh bisa menjadi seorang penulis. Selain itu, para peserta juga memperoleh gambaran tentang prosedur mempublikasikan karya ke berbagai media cetak.